Nurse Credentialing, Work Motivation, and Performance: A Cross-Sectional Mediation Study - Ahsan, Ahsan; Wokas, Deyfi Christine; Yuliatun, Laily (Chakra Brahmanda Lentera Institute, 2026)
Background: Nurse credentialing is intended to ensure professional competence, improve performance, and enhance work motivation. However, despite its widespread implementation, evidence regarding its actual impact on nurses’ motivation and performance remains inconsistent and inconclusive. This inconsistency reflects an unresolved gap in understanding whether credentialing directly influences nurse performance or operates indirectly through work motivation. This study aimed to examine the relationship between credentialing, work motivation, and nurse performance, with work motivation tested as a mediating variable. Methods: This quantitative cross-sectional study followed the STROBE reporting guideline. The population comprised all inpatient nurses at Dr. Sam Ratulangi Tondano Regional General Hospital (N = 176). Using purposive sampling, 122 nurses were selected based on inclusion criteria of at least one year of work experience and direct involvement in nursing care; nurses on leave were excluded. Credentialing level (PK0–PK3) was the independent variable, nurse performance the dependent variable, and work motivation the mediating variable. Motivation and performance were measured using validated Likert-scale questionnaires, while credentialing data were obtained from institutional records. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to test direct and mediating effects. Results: Credentialing showed a negligible and non-significant effect on nurse performance (β = 0.002; p = 0.979) and work motivation (β = 0.027; p = 0.683). Conversely, nurse performance had a strong and significant effect on work motivation (β = 0.768; p < 0.001). Work motivation did not mediate the credentialing–performance relationship. Conclusion: Credentialing alone does not significantly influence nurse performance or motivation. Integrating credentialing with performance management and continuous professional development systems is essential to enhance its effectiveness